Comprehensible Input to Promote Effective Language Output (2017)
ABSTRACT: This is the report of an action research study whose purpose was to explore to what extent providing students with comprehensible input can promote students’ effective language output. Data was collected through my research journal, a survey to students, an interview with the teacher, my teacher’s advisor class observation report, and some students’ artifacts. The data analysis revealed that when students are provided with the necessary input, clear instructions and feedback, their written and oral productions are more accurate. They also become more participative, more engaged and motivated toward the class, and they feel free of expressing their ideas in a more critical way using the language they have been taught. Key words: input, output, instructions, feedback, critical media literacy.